Case Report: Aplastic anemia related to a novel CTLA4 variant - Hall, Geoffrey; Markle, Janet G.; Maiarana, James; Martin, Paul L.; Rothman, Jennifer A.; Sleasman, John W.; Lederman, Howard; Azar, Antoine E.; Brodsky, Robert A.; Mousallem, Talal (Frontiers in Pediatrics, 2024)
A 20-year-old male patient with a history of celiac disease came to medical attention after developing profound fatigue and pancytopenia. Evaluation demonstrated pan-hypogammaglobulinemia. There was no history of significant clinical infections. Bone marrow biopsy confirmed hypocellular marrow consistent with aplastic anemia. Oncologic and hematologic evaluations were unremarkable for iron deficiency, paroxysmal nocturnal hemoglobinuria, myelodysplastic syndromes, T-cell clonality, and leukemia. A next generation genetic sequencing immunodeficiency panel revealed a heterozygous variant of uncertain significance in CTLA4 c.385T >A, p.Cys129Ser (C129S). Cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) is an inhibitory receptor important in maintaining immunologic homeostasis. To determine the functional significance of the C129S variant, additional testing was pursued to assess for diminished protein expression, as described in other pathogenic CTLA4 variants. The results demonstrated severely impaired CTLA-4 expression and CD80 transendocytosis, consistent with other variants causing CTLA-4 haploinsufficiency. He was initially treated with IVIG and cyclosporine, and became transfusion independent for few months, but relapsed. Treatment with CTLA-4-Ig fusion protein (abatacept) was considered, however the patient opted for definitive therapy through reduced-intensity haploidentical hematopoietic stem cell transplant, which was curative.